Analysis of Morphological Errors on Speech and Communication Styles of UIN North Sumatra Students - Anggi Dwi Rosidi Nasution; Athiyya Azzahra; Fitra Audina; Muhammad Alfin Rangkuti; Susanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Language errors are caused by deviations from language rules. There are language rules in communication that must be considered. This study is a series of activities related to methods of collecting library data, as well as activities related to reading, storing and processing research materials from journals and books on the internet, as well as textbooks related to the study of morphology.errors. in Student Speeches. and communication style. All data must be matched to the identified research topic to be collected. To adapt to a new area, most students from outside the area use Indonesian to facilitate communication. This is one solution to avoid understanding caused by cultural differences between UIN Sumut Medan students.